2022
DOI: 10.1093/ptj/pzab314
|View full text |Cite
|
Sign up to set email alerts
|

Manual Lymph Drainage With Progressive Arm Exercises for Axillary Web Syndrome After Breast Cancer Surgery: A Randomized Controlled Trial

Abstract: Objective This study aimed to determine the effectiveness of a physical therapist–designed program tailored to axillary web syndrome (AWS) in women after breast cancer surgery. Methods A prospective, single-center, assessor-blinded, randomized controlled trial was conducted at the Physiotherapy in Women’s Health Research Unit of the Alcalá University (Madrid, Spain). Ninety-six women with AWS were assigned to the physical the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This physical therapy protocol also resulted in no adverse events [10]. Torres-Lacomba et al compared physiotherapy with and without manual lymphatic drainage in an RCT and found that manual lymphatic drainage helped reduce pain [5]. It is expected that physiotherapy protocols for AWS after breast cancer surgery will become standardized in the future.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This physical therapy protocol also resulted in no adverse events [10]. Torres-Lacomba et al compared physiotherapy with and without manual lymphatic drainage in an RCT and found that manual lymphatic drainage helped reduce pain [5]. It is expected that physiotherapy protocols for AWS after breast cancer surgery will become standardized in the future.…”
Section: Discussionmentioning
confidence: 98%
“…Although lymphatic involvement has been suggested, the detailed pathophysiology of AWS remains unclear [4,5]. In a study in which lymphoscintigraphy was performed in patients with AWS, it was reported that approximately 90% of the patients had changes such as decreased lymphatic function and obstruction of lymphatic vessels and 67% had collateral lymphatic vessels.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, rehabilitation might positively impact AWS prevention, pain management, and AWS treatment after BC surgery [27]. However, despite the wide variability of rehabilitative approaches proposed in the current literature, to date, the optimal rehabilitation strategies to manage AWS are far from being fully understood [26].…”
Section: Introductionmentioning
confidence: 99%